Molecular properties of human IgG subclasses and their implications for designing therapeutic monoclonal antibodies against infectious diseases - Irani, V.; Guy, A.; Andrew, D.; Beeson, J.; Ramsland, Paul; Richards, J. (Elsevier Ltd, 2015)
Monoclonal antibodies are being developed as therapeutics to complement drugs and vaccines or to fill the gap where no drugs or vaccines exist. These therapeutic antibodies (ThAb) may be especially important for infectious diseases in which there is antibiotic resistance, toxin-mediated pathogenesis, or for emerging pathogens. The unique structure of antibodies determines the specific nature of the effector function, so when developing ThAb, the desired effector functions need to be considered and integrated into the design and development processes to ensure maximum efficacy and safety. Antibody subclass is a critical consideration, but it is noteworthy that almost all ThAb that are licenced or currently in development utilise an IgG1 backbone. This review outlines the major structural properties that vary across subclasses, how these properties affect functional immunity, and discusses the various approaches used to study subclass responses to infectious diseases. We also review the factors associated with the selection of antibody subclasses when designing ThAb and highlight circumstances where different subclass properties might be beneficial when applied to particular infectious diseases. These approaches are critical to the future design of ThAb and to the study of naturally-acquired and vaccine-induced immunity.